Strategi Wirausahawan Muda menghadapi Era Society 5,0 di Kota Surabaya (Studi Kasus pada Kalihkitha Wedding Organizer) - Veny Purwanti; Nuansa Bayu Segara; Kusnul Khotimah; Dian Ayu Larasati (Program Studi Pendidikan IPS Unesa, 2022)
The main focus of this research is to find out the strategies used by young entrepreneurs in facing the era of society 5.0 in the city of Surabaya by using a case study on the Kalihkitha Wedding Organizer, as well as to find out the relevance of the strategies used by young entrepreneurs in facing the era of society 5.0. This research is a type of qualitative research that collects data using observation, interviews, and document analysis. The method used for data analysis uses the Miles and Huberman analysis model by means of data reduction, data presentation, and conclusion drawing or verification. In addition, this study also uses triangulation, namely by using data sources, theories, and methods. In this research, researchers found that there are three strategies used by entrepreneurs, namely concept planning, strategy implementation, and strategy evaluation. In addition, it was found that the relevance of the activities carried out by Kalihkitha entrepreneurs related to the social studies learning objectives, namely the independent learning curriculum. The points associated are the community's efforts to meet the necessities of life and analyze the development of the digital economy.